Mucinous Tubular and Spindle Cell Carcinoma of the Kidney with Sarcomatoid Differentiation - Simon, Rochelle A (e-Century Publishing Corporation, 2008)
We report a unique case of mucinous tubular and spindle cell carcinoma (MTSC) of the kidney with extensive sarcomatoid differentiation, multiple metastases, and a rapidly fatal clinical course. The patient presented with back pain and a pathologic L1 fracture. Diagnostic imaging revealed a large retroperitoneal mass arising from the left kidney and compressing the spinal cord. Radiotherapy and surgery were performed, but the patient died from disease progression three weeks postoperatively. MTSC is a recently recognized entity that is considered to be a low-grade carcinoma with a favorable prognosis. Our case demonstrates that although MTSC is usually a low-grade carcinoma, sarcomatoid differentiation may occur and lead to a fatal course, as in all other types of renal cell carcinomas. Adequate sampling and the exclusion of sarcomatoid differentiation in the spindle cell component are necessary for proper management and prognostication. To our knowledge, this is the first reported case of MTSC with sarcomatoid differentiation and a fatal outcome.